Legal Consequences of the Examination Results of the Tax Object Value Based on Fair Market Price in Land Sale Transactions - Reni Anggraini (Indonesian Journal of Law and Economics Review, 2018)
Acquisition of land and building rights raises rights and obligations for holders and recipients of rights, namely paying customary taxes on land rights. The implementation of the payment of Customs Tax on the Right to Land and Building must be accompanied by the results of the examination of the value of the tax object on the Acquisition Duty of the Right to Land and Building which has been determined by the Regional Tax Service Agency based on Fair Value. The purpose of this thesis is to find out the legal consequences of the examination of the tax object value at the acquisition cost of land and building rights based on fair value. The method used in this thesis uses the normative research method of the statute approach. The benefits of the research as a material for research on the contribution of thought so that the wider community can find out about the legal consequences of the research results of the value of tax object acquisition on the acquisition of land and building rights based on fair value.